MATERNAL FACTORS ASSOCIATED WITH CHILD NUTRITION IN RICE-BASED FARM HOUSEHOLDS IN CENTRAL LUZON, PHILIPPINES (Proceedings of the International Conference on Public Health, 2017)
Mothers play key roles in the development of children’s eating behavior, food consumption, and nutrition. This study primarily aimed to determine the maternal factors associated with child nutrition. A cross-sectional community survey was conducted in rice-based farm households in Central Luzon to obtain anthropometric measurements from 275 children 0 to 10 years old and their mothers. Socio-demographics were collected on mothers. Mothers’ knowledge level on health and nutrition was also assessed. Among pre-school children, stunting (15.2%), underweight (16.8%), and wasting (19.5%) were low, medium, and very high, respectively. The corresponding figures in school-age children were 16.9%, 18.9%, and 22.1%. Compared with males, female children exhibited higher prevalence in almost all malnutrition indicators (stunting, wasting, and underweight), pre-school age (16.9% to 20.4% vs 16.7% to 19%) and school-age (13.7% to 25.5% vs 19.1% to 23.1%). Logistic regression analyses revealed that low educational attainment for mothers [AOR=2.78 (CI: 1.03, 7.48)] and low household income [AOR=2.28 (CI: 01.08, 4.82)] led to higher odds of underweight. Absence of a major illness or disability [AOR=0.33 (CI: 0.12, 0.87)] in mothers resulted in lower odds of wasting. Mothers with lower BMI [AOR=5.47 (CI: 1.43, 20.95)] and non-membership in organizations (e.g. farmers association) [AOR=2.21 (CI: 1.12, 4.35)] led to higher odds of wasting. Living in rural areas [AOR=2.61 (CI: 1.22, 5.57)] resulted in higher odds of stunting. Maternal factors such as education, nutritional and health status, and other factors such as income and place of residence were associated with the occurrence of malnutrition in children. Hence, this study recommends gender-sensitive nutrition interventions directed to mothers for improved child nutrition.
Keywords: anthropometric data, child nutrition, maternal factors, stunting, underweight, wasting